Apolipoprotein C-III Strongly Correlates with Activated Factor VII–Anti-Thrombin Complex: An Additional Link between Plasma Lipids and Coagulation - Martinelli, Nicola; Baroni, Marcello; Castagna, Annalisa; Lunghi, Barbara; Stefanoni, Filippo; Tosi, Federica; Croce, Jacopo; Udali, Silvia; Woodhams, Barry; Girelli, Domenico; Bernardi, Francesco; Olivieri, Oliviero (Thrombosis and Haemostasis, 2019)
Activated factor VII–anti-thrombin (FVIIa-AT) complex is a potential biomarker of pro-thrombotic diathesis reflecting FVIIa–tissue factor (TF) interaction and has been associated with mortality in patients with coronary artery disease (CAD). Previous data indicated plasma lipids as predictors of FVIIa-AT variability, and plasma lipoproteins as potential stimulators of the coagulation cascade. Our aim was to evaluate the relationships between FVIIa-AT plasma concentration and a broad apolipoprotein profile (including ApoA-I, ApoB, ApoC-III and ApoE). Within the framework of the observational Verona Heart Study, we selected 666 subjects (131 CAD-free and 535 CAD, 75.4% males, mean age: 61.1 ± 10.9 years) not taking anticoagulant drugs and for whom plasma samples were available for both FVIIa-AT assay and a complete lipid profile. Plasma concentration of FVIIa-AT levels significantly and directly correlated with total and high-density lipoprotein cholesterol, triglycerides, ApoA-I, ApoC-III and ApoE levels. ApoC-III showed the strongest correlation (R = 0.235, p = 7.7 × 10−10), confirmed in all the sub-group analyses (males/females and CAD/CAD-free). Only ApoC-III remained associated with FVIIa-AT plasma concentration, even after adjustment for sex, age, CAD diagnosis, body mass index, renal function, smoking status, lipid-lowering therapies and FVIIa levels. The APOC3 gene locus-tagging polymorphism rs964184, previously linked with cardiovascular risk and plasma lipids by genome-wide association studies, was associated with both ApoC-III and FVIIa-AT plasma concentration. Our results indicate a strong association between ApoC-III and FVIIa-AT levels, thereby suggesting that an increased ApoC-III concentration may identify subjects with a pro-thrombotic diathesis characterized by an enhanced TF-FVIIa interaction and activity.
Keywords: activated factor VII–anti-thrombin complex; APOC3 gene polymorphism; apolipoprotein C-III; coagulation; plasma lipids